Natural products target programmed cell death signaling mechanisms to treat colorectal cancer - Zheng, Ya; Feng, Na; Li, Canglin; Li, Zuoqiang (Frontiers in Pharmacology, 2025)
As a highly prevalent gastrointestinal malignant tumor, colorectal cancer poses a serious challenge in terms of increasing morbidity and mortality and late diagnosis due to the invisibility of the disease. Although existing therapies are diverse but limited in efficacy, the mechanism of programmed cell death (PCD) has become a focus of research due to its central role in maintaining body homeostasis and regulating tumor progression. Multimodal cell death pathways, such as apoptosis, autophagy, pyroptosis and ferroptosis, have shown unique advantages in inhibiting the proliferation and migration of colorectal cancer cells and enhancing the sensitivity to chemotherapy by responding to internal and external environmental stimuli. In recent years, natural products have risen to prominence by virtue of their multi-target synergistic effects and chemo-sensitizing properties, and have opened up a new direction for colorectal cancer treatment by precisely regulating the PCD pathway. In this paper, we searched PubMed, Web of Science and CNKI databases for relevant studies in the last 10 years using the keywords (Colorectal cancer) and (programmed cell death) and natural products. This work retrieved 59 studies (55 from the past 5 years and 4 from the past 10 years) to reveal the mechanism of action of natural products targeting PCD, aiming to provide theoretical support and practical guidance for the optimization of clinical therapeutic strategies and the development of innovative drugs.